Pencegahan Kekerasan terhadap Anak: Sebuah Perspektif Psikologis tentang Ketahanan Keluarga - Syaidah, Khasnah; Rohmah, Siti; Hendra, Tomi (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
Abstract. Child abuse, with its devastating physical and psychological consequences, underscores the critical need for protective family environments. This study employed a literature review to explore the psychological underpinnings of family resilience as a preventive strategy. The research aimed to identify and delve into the physical, social, psychological, and spiritual dimensions of family resilience in relation to child abuse prevention. A systematic literature review was performed, searching for relevant publications, including books, journal articles, and conference proceedings, using Google Scholar. Findings emphasize a holistic approach to building family resilience, encompassing physical health, strong family bonds, effective stress management, emotional regulation, and spiritual grounding. These components collectively contribute to a protective environment that shields children from abuse.